Climate change impact in the Ria de Aveiro lagoon ecosystem: a case study - Lopes, José Fortes (2021)
Climate change and global sea-level rise are major issues of the 21st century. The main goal of this study is to assess the physical and biogeochemical status of the Ria de Aveiro lagoon (Portugal) under future climate scenarios, using a coupled physical/ eutrophication model. The impact on the lagoon ecosystem status of the mean sea level rise (MSLR), the amplitude rise of the M2 tidal constituent (M2R), the changes in the river discharge, and the rising of the air temperature was investigated. Under MSLR and M2R, the results point to an overall salinity increase and water temperature decrease, revealing ocean water dominance. The main lagoon areas presented salinity values close to those of the ocean waters (~34 PSU), while a high range of salinity was presented for the river and the far end areas (20–34 PSU). The water temperature showed a decrease of approximately 0.5–1.5 C. The responses of the biogeochemical variables reflect the increase of the oceanic inflow (transparent and nutrient-poor water) or the reduction of the river flows (nutrient-rich waters). The results evidenced, under the scenarios, an overall decreasing of the inorganic nitrogen concentration and the carbon phytoplankton concentrations. A warm climate, although increasing the water temperature, does not seem to a ect the lagoon’s main status, at least in the frame of the model used in the study.